Management of extensive surgical emphysema with subcutaneous drain: A case report. (2018) - Tran, Quoc; Mizumoto, Ryo; Mehanna, Daniel
Highlights: Subcutaneous emphysema usually follows a benign course, in severe cases it can be debilitating and often requires intervention. Subcutaneous emphysema managed with large-bore drain, maintained on low suction. Simple, safe option with sustained decompression of subcutaneous emphysema. Abstract: Introduction: Subcutaneous emphysema (SE) is a frequent and often self-limiting complication of tube thoracostomy or other cardiothoracic procedures. On rare occasions, severe and extensive surgical emphysema marked by palpable cutaneous tension, dysphagia, dysphonia, palpebral closure or associated with pneumoperitoneum, airway compromise, "tension phenomenon" and respiratory failure require treatment. Presentation of case: A 67 year old lady presented with a large spontaneous pneumothorax on the background of end-stage chronic obstructive pulmonary disease (COPD) and newly diagnosed lung cancer, developed extensive surgical emphysema following insertion of a chest drain. Immediate improvement was observed after insertion of a large-bore, 26 French (Fr.) intercostal catheter, subcutaneous drain which was maintained under low suction (−5 cm H2 O) for a further 24 h. Discussion: Several methods have been described in the literature for the treatment of extensive subcutaneous emphysema, including: emergency tracheostomy, multisite subcutaneous drainage, infraclavicular "blow holes" incisions and subcutaneous drains or simply increasing suction on an in situ chest drain. Here a large-bore, fenestrated, subcutaneous drain maintained on low negative pressure also provided the necessary decompression. Conclusion: In the absence of a comparative study to identify the most effective method to manage extensive subcutaneous emphysema, this case highlights an effective, simple and safe management option.